The Effects of Varying Concentrations of Didecyl Methylpropyl Ammonium Iodide (DMPAI) on the Structure and Function of Soil Bacterial Communities in the Lake–Terrestrial Ecotone - Qi Zhu; Lingquan Zeng; Chunhua Li; Chun Ye (Microorganisms)
To address freshwater lake blooms resulting from eutrophication, the application of quaternary ammonium compounds as algaecides serves as an effective emergency remediation strategy. Didecyl methylpropyl ammonium iodide (DMPAI) is a novel quaternary ammonium algaecide; however, its bacteriostatic properties may significantly disrupt the microbial activity in lakes, particularly within the lake–terrestrial ecotone. To investigate the degradation process of DMPAI in the lake–terrestrial ecotone and its impact on the microbial community, experiments were conducted using a large-scale indoor simulation device to analyze DMPAI concentrations, the composition of the lake microbial community, and associated gene functions. The results showed that (1) DMPAI was completely removed from the lake water body in approximately 36 h; (2) The addition of DMPAI altered the microbial community structure in the lake–terrestrial ecotone, as evidenced by an increase in the diversity index and the proliferation of microorganisms capable of tolerating and degrading DMPAI, such as Pseudomonas and Flavobacterium, within a short period. These changes were typically observed after 10 d and generally recovered, not persisting for extended periods. (3) Functional genes involved in carbon, nitrogen, and sulfur cycling are more significantly impaired in the lake–terrestrial ecotone with DMPAI addition. The destabilization of the microbial community may lead to a short-term increase in pathogenic bacteria during the recovery process. This phenomenon was more pronounced in environments with higher concentrations of DMPAI. Therefore, the concentration of DMPAI should be controlled within the range of 0.5 to 2.0 mg L−1.